2022
DOI: 10.1111/jcap.12399
|View full text |Cite
|
Sign up to set email alerts
|

Family lifestyle is related to low‐income preschoolers' emotional well‐being during COVID‐19 pandemic

Abstract: Problem COVID‐19 has profoundly impacted children's behavioral and psychosocial development, especially young children from low‐income families. This study examined how caregivers' and preschoolers' lifestyle behaviors (sleep, screen time, physical activity, eating behavior) were related to preschoolers' emotional well‐being (sadness, fear, anger, and positive affect). Methods Using a cross‐sectional design, we recruited low‐income caregivers from Head Start organizations and the Qualtrics panel. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Thus, our study provides an original contribution to the literature by capturing US caregivers' views of their families' physical and mental health challenges and their coping strategies during the pandemic. While most of the existing studies used a quantitative approach (e.g., Karpman et al, 2020; Ling et al, 2023; Robbins & Ling, 2022), our study used a qualitative phenomenological approach to examine lifestyle behavior and mental health changes incurred by COVID‐19. We analyzed participants' qualitative voices to provide important insights regarding the compounding effects of COVID‐19 on caregivers and preschoolers in the US.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our study provides an original contribution to the literature by capturing US caregivers' views of their families' physical and mental health challenges and their coping strategies during the pandemic. While most of the existing studies used a quantitative approach (e.g., Karpman et al, 2020; Ling et al, 2023; Robbins & Ling, 2022), our study used a qualitative phenomenological approach to examine lifestyle behavior and mental health changes incurred by COVID‐19. We analyzed participants' qualitative voices to provide important insights regarding the compounding effects of COVID‐19 on caregivers and preschoolers in the US.…”
Section: Discussionmentioning
confidence: 99%
“…According to SCM, COVID-19 is a strong stimulus that plausibly induces people to perceive high risk of infection which could lead to severe mental and behavior problems [ 3 ]. Many studies found that the potential to contract a highly lethal disease, such as COVID-19, can overwhelm people emotionally and physically, and induce strong mental and behavioral responses [ 4 , 5 , 7 , 33 , 34 ]. Sleep, emotional, and lifestyle problems are common manifestation of mental and behavioral problems [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research on the OWB of residents mainly focuses on the relationship between cultural ecosystem service value [34,35], medical treatment [36], and leisure transportation [37] in nature reserves. The study of OWB is mainly based on external indicators that reflect residents' objective economic and social living conditions, such as relative income [38,39], expenditure structure [40], employment status [41], physical health indicators [42], social security [43], and other aspects. Among other factors, education, entertainment, aesthetics, and escapism promote well-being [44], mainly in the process of tourism consumption [45], which can better promote the quality of life and happiness of residents.…”
Section: Introductionmentioning
confidence: 99%